Cetacean conservation in the Mediterranean and Black Seas: Fostering transboundary collaboration through the European Marine Strategy Framework Directive. (August 2017) - Authier, Matthieu; Commanducci, Florence Descroix; Genov, Tilen; Holcer, Draško; Ridoux, Vincent; Salivas, Maÿlis; Santos, M. Begoña; Spitz, Jérôme
Abstract: The European Marine Strategy Framework Directive (MSFD) aims at implementing a precautionary and holistic ecosystem-based approach for managing European marine waters. Marine mammals are included as a functional group for the assessment and reporting under Descriptor 1-Biodiversity. Conservation of mobile marine megafauna such as cetaceans requires transboundary cooperation, which the MSFD promotes through regional instruments, such as the Regional Sea Conventions and other regional cooperation structures such as ACCOBAMS (Agreement on the Conservation of Cetaceans of the Black Sea, Mediterranean Sea and Contiguous Atlantic Area). A questionnaire survey and an exploratory analysis of MSFD implementation in the Mediterranean and Black Seas were conducted. The analysis revealed (i) the saliency of cetacean conservation, and (ii) heterogeneity among countries in the implementation of the MSFD that may hinder transboundary collaboration. ACCOBAMS can stimulate collaboration among scientists involved in cetacean monitoring and can foster transboundary initiatives that would align with MSFD objectives. Highlights: Cetacean conservation requires transboundary collaboration. Lack of collaboration among EU Member States undermines MSFD implementation. ACCOBAMS can promote greater cooperation between EU and non-EU ACCOBAMS Parties.